Design of Hollow-Rotor Brushless DC Motor - Raja Nor Firdaus Raja Othman; Farina Sulaiman; Suhairi Rizuan; Kasrul Abdul Karim; Auzani Jidin; Tole Sutikno; Norhisam Misron (International Journal of Power Electronics and Drive Systems (IJPEDS), 2016)
This paper discusses about design of hollow-rotor Brushless DC (BLDC) motor. A conventional BLDC motor has more leakage flux circling at the end of the permanent magnet that will limit torque. To overcome this problem, a new BLDC model known as hollow-rotor is proposed. The objective of this research is to design a hollow-rotor motor that will have higher torque density compared to conventional BLDC motor using Finite Element Method (FEM). In addition, performance analysis of the proposed hollow-rotor has also been carried out. For validation, the result of FEM is compared with the measurement result. It shows that, the simulation result has good agreement with the measurement result. For comparison, hollow-rotor shows higher torque density compared to conventional BLDC motor. As a conclusion, this paper provides guidelines and analysis in designing high torque hollow-rotor motor.